Pengupahan Buruh Panen Padi di Desa Pagersari, Mungkid, Magelang (Analisis Hukum Islam) - Aprilia Risma Yanti (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2019)
Wage of paddy labors in villages is mostly based on heredity habits. This practice occurs continuously in muamalah activities as in Pagersari village, Mungkid, Magelang. This research aims to analyze the wage of paddy labors in Pagersari village by looking at the condition of the people who do not understand the conformity of the practice with the  Islamic law rules about wage. The method used in this research was descriptive analysis with qualitative approach. The data collection techniques were using interviews, field studies, and documentation studies. Meanwhile the data analysis techniques covered the data reduction, the data presentation, and conclusion drawing. This research was done by people who practice the wage of paddy labors. The result of the research shows that those practices according to Islamic law are categorized in fikih muamalah; that is ijarah based on works (ijarah ala al amal) which has been fulfilled the contract basis (rukun akad). The wage received is bawon gabah with the comparison system 12:1, 13:1, and 14:1 from the harvest which is divided between the laborers and the farmers in kilogram units. The wage is categorized ajrul misli; that is worth it with the works and the working conditions. As seen from the appropriateness in Islamic law, the wage practice has fulfilled the worthiness and virtue elements. It just has not fulfilled the element of justice in the form of transparency in the distribution of wage in the balance.